Attitudes towards influenza vaccine and a potential COVID-19 vaccine in Italy and differences across occupational groups, September 2020: Attitudes towards influenza vaccine and a potential COVID-19 vaccine in Italy - La Vecchia, Carlo; Negri, Eva; Alicandro, Gianfranco; Scarpino, Vilma (La Medicina del Lavoro, 2020)
Objectives: We aimed at describing the attitudes towards influenza vaccination and a potential COVID-19 vaccine in Italy. Methods: A nationally representative survey based on 1055 Italians aged 15-85 years was conducted in September 16-28, 2020. Results: We found that 40.8% of the population reported the intention to be vaccinated against influenza next winter and 53.7% would accept to receive a potential COVID-19 vaccine. The percentages were higher among individuals aged 55 and over (58.8% for influenza vaccine and 58.2% for a potential COVID-19 vaccine) and among professionals, managers and teachers as compared to manual workers and farmers (36.1% vs. 27.6% for influenza vaccine and 51.6% vs. 44.8% for a potential COVID-19 vaccine). Discussion: These data confirm a certain degree of vaccine mistrust in Italy, especially among less qualified workers.